The PI3K/AKT Pathway—The Potential Key Mechanisms of Traditional Chinese Medicine for Stroke - Gu, Chenyang; Zhang, Qiankun; Li, Yajing; Li, Rong; Feng, Jia; Chen, Wanghao; Ahmed, Waqas; Soufiany, Ismatullah; Huang, Shiying; Long, Jun; Chen, Lukui (Frontiers in Medicine, 2022)
Stroke is associated with a high disability and fatality rate, and adversely affects the quality of life of patients and their families. Traditional Chinese Medicine (TCM) has been used effectively in the treatment of stroke for more than 2000 years in China and surrounding countries and regions, and over the years, this field has gleaned extensive clinical treatment experience. The Phosphatidylinositol 3 kinase (PI3K)/ protein kinase B (AKT) pathway is important for regulation of cell migration, proliferation, differentiation, and apoptosis, and plays a vital role in vascularization and oxidative stress in stroke. Current Western medicine treatment protocols for stroke include mainly pharmacologic or mechanical thrombectomy to restore blood flow. This review collates recent advances in the past five years in the TCM treatment of stroke involving the PI3K/AKT pathway. TCM treatment significantly reduces neuronal damage, inhibits cell apoptosis, and delays progression of stroke via various PI3K/AKT-mediated downstream pathways. In the future, TCM can provide new perspectives and directions for exploring the key factors, and effective activators or inhibitors that affect occurrence and progression of stroke, thereby facilitating treatment. (Graphical Abstract)